HUBUNGAN ANTARA UMUR DAN PARITAS IBU DENGAN KEJADIAN INTRA UTERINE FETAL DEATH (IUFD) DI RSUD KOTA PRABUMULIH TAHUN 2021 - Eka Juniarty; Dwi Saputri Mayang Sari (LPPM STIKes Mitra Adiguna, 2023)
According to the World Health Organization (WHO), in 2017 the Infant Mortality rate (IMR) in the world 29 per 1,000 live births, Underfive Mortality Rate (AKBA) 12 per 1,000 live births. The Neonatal Mortality Rate (MMN) decreases with the IDHS (Demographic and Health Indonesia Survey) 15 per 1,000 live births by 2017 (MoH RI, 2011). The purpose of this study was to determine the relationship between maternal age and parity on intra uterine fetal deadth (IUFD) occurrence in the general hospital on Prabumulih City 2021. This research uses Analytical Survey by using Cross Sectional approach. The population of this study were all babies born in the general hospital on Prabumulih City 2021, amounting to 1798 people. The number of samples in this study were 327 respondents. In the analysis of univariate, it was found that from 327 respondents found that maternal parity that high risk of childbirth as much as 44 respondents (13.5%) fewer than parity mother which low risk giving birth that is counted 283 respondents (86.5%). The result of univariate analysis obtained from 327 respondents found that maternal parity that high risk of childbirth as much as 61 respondents (18,7%) fewer than parity mother which low risk giving birth that is counted 266 respondent (81,3%). Bivariate analysis showed that maternal age had significant relationship with incidence of IUFD (p value 0,000) and mother parity had significant relationship with incidence of IUFD (p value 0,000). The conclusion of this study is there is a significant relationship between maternal age and parity against intra uterine fetal deadth (IUFD) occurrence in the generah hospital on Prabumulih City 2021 Keywords : Age, parity of mother and occurrence of IUFD References : 17 (2017-2021)